PENINGKATAN PENGETAHUAN TENTANG NARKOBA SEBAGAI UPAYA GOTONG ROYONG DALAM MELAWAN PENYALAHGUNAAN NARKOBA - Bangsawan, Try Adhi; Amilia, Rizki; Raditya, Mukhlis; Anisa, Neng Putri; Werdia, Tia; Dayanti, Sri; Sari, Indah (Nindikayla Institute, 2023)
Community Service Activities (PKM) aim to socialize about drug prevention in Alang-alang Village to the RT.RW and local village apparatus. The method of implementation in this community service is carried out using a socialization or dissemination strategy through discussion forums with the community which are RT/RW and Alang-alang Village Apartments, and to measure the results of this activity are pre-test and post-test. Partners have additional knowledge related to narcotics, especially in Alang-alang Village. The involvement of various community elements also adds to the understanding that automotive is not only the responsibility of the government, but also a shared responsibility. The results of this activity are the average results in the range of 70-90% of participants understand the dangers of drugs for body health, know how to handle them, feel the benefits of this socialization, know the important role of the family in reflecting on drugs and know the dangers of drugs for health.